Monopoly Game Media as an Effort to Improve Calculation Problem Solving Ability in Elementary School Students - Mohammad Archi Maulyda; Vivi Rachmatul Hidayati; Muhammad Erfan ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
This development research was motivated by the information that the student's average score on the material for solving calculation problems, including those related to money, was still below the KKM (70). One of the reasons is that the teacher does not use the media to teach the material. To overcome this problem, it is necessary to develop media in accordance with the material. The data collection instrument in this study is a checklist sheet with observation and test techniques. The data analysis technique used is quantitative and descriptive qualitative data analysis. The development model for developing monopoly media refers to a development model with the ADDIE approach which includes 5 stages, namely analysis, design, development, implementation, and evaluation. The conclusion of the results of this study is that the monopoly game media is declared valid after being revised by material experts and media experts with a score of 75% which belongs to the B criteria with the Good category The effectiveness of the media in increasing the ability to solve calculation problems, including those related to money, by using the development of monopoly games for grade III students of SDN 4 Cakranegara, Mataram